Blended Learning as a Supporter of the Synergy of Academic Guidance and AI Technology in Scientific Writing - Eka Nurjanah; Moh. Zainudin (Indonesia Civil Pilot Academy Banyuwagi, 2026)
This study examined students’ perceptions of the integration of blended learning, academic supervision, and artificial intelligence (AI) technologies in the scientific writing process. Employing a qualitative research design, data were collected through semi-structured interviews, observations, and document analysis involving undergraduate students who had participated in academic writing supervision and used AI-based tools. The findings showed that blended learning provided greater flexibility, enhanced self-regulated learning, and improved students’ engagement in academic writing. Students reported that AI tools such as ChatGPT and Grammarly offered instant feedback, assisted in generating ideas, and supported linguistic accuracy, although concerns regarding originality and the need for critical evaluation of AI-generated outputs remained. The integration of AI and blended learning was found to be effective only when it was accompanied by continuous academic supervision. This study concluded that the synergy of the three components created an adaptive and supportive learning ecosystem that significantly improved the structure, coherence, and analytical depth of students’ scientific papers.